3D.08: ARTERIAL STIFFNESS AND AUTONOMIC NERVOUS FUNCTION ON ORTHOSTATIC BLOOD PRESSURE-ELEVATION IN HYPERTENSIVE PATIENTS. (June 2015) - Kaneta, M.; Miyai, N.; Yamamoto, M.; Oka, M.; Utsumi, M.; Shiba, M.; Arita, M.
Abstract : Objective: Using a simple standing-up test in hypertensive patients, we evaluated orthostatic upright postural blood pressure (BP) changes and autonomic nervous function, as well as the relationship between orthostatic BP-elevation and subclinical markers of atherosclerosis. Design and method: A total of 351 hypertensive patients aged 35–75 years (60.4 ± 8.7 years) were enrolled. We measured body mass index (BMI), systolic BP (SBP) and diastolic BP (DBP) and subclinical markers of atherosclerosis. Brachial ankle pulse wave velocity (baPWV), late systolic peak of the pressure wave form (SBP2) and carotid mean IMT were measured. Participants underwent a simple standing-up test involving sitting then standing for 2 minutes each, followed again by sitting. To evaluate autonomic fluctuations, we calculated the coefficient of variation of the R-R interval, the ratio of low to high frequency heart rate variability (LF/HF), and the coefficient of component variance of high frequency. Results: Orthostatic hypotension (OH: δSBP < −20 mmHg) and hypertension(OHT: δSBP > 10mmHg) was assessed with blood pressure measurements in sitting and standing position. OH was present in 30, normal response in 283, and OHT was 38 patients. OH was excluded in this study. Significant correlations were found between baPWV and resting SBP(r 2  = 0.462, P < 0.001) and sympathetic α function(r 2  = 0.177, p < 0.01). In OHT group, δSBP(15.0 vs-3.25mmHg;p < 0.0001), δDBP(3.3 vs -0.27mmHg;p < 0.001), baseline SBP(145.4 vs 138.7mmHg;p-0.02), SBP2(134.6 vs 125.9mmHg; p = 0.001), baPWV(1757 vs 1637 mm/s; p = 0.014), LF/HF at standing(6.17 vs 3.86; p = 0.015), CVRR at standing (2.95 vs 2.56; p = 0.031)were significantly higher than in OHT(-) group. Multiple regression analyses showed that an increase in SBP as well as baseline SBP, age, BMI, were independent determinants of PWV. Conclusions: We have shown that increased arterial stiffness and autonomic nervous function in the hemodynamic response was associated with OHT during a standing-up test. Arterial stiffness may contribute to greater BP elevation to postural changes from standing.